Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan UIN Sunan Kalijaga Yogyakarta - Sulistyaningsih Sulistyaningsih; Ambar Sari Dewi; Yani Tri Wijayanti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
The ttransformation of IAIN (State Islamic Institute) Sunan Kalijaga becomes a StateIslamic University (UIN) Sunan Kaijaga has demand a reformation and one of them is in thefield of human resources governance. The human resources has become one of the importantassets for the sustainability of the activityies in the UIN Sunan Kalijaga. Human resourcesat UIN Sunan Kalijaga include: (1) lecturers, (2) administrative personnel, (3) of functionalstaff except lecturers (researchers, librarians, and archivists). Along with progress in thetransformation into a university, UIN Sunan Kalijaga has received ISO 9001:2008 from TUVRheiland on September 10, 2009. This study focuses on the services provided by employees(personnel administration). In its implementation on the ground was still found how the performanceof employees at UIN Sunan Kalijaga have not maximum and satisfy yet. Based onthis background, this study proposed the formulation of the problem as follows: Is there anyinfluence of organizational culture on the employee performance in UIN Sunan Kalijaga Yogyakarta?Theory used in this study is the theory related to organizational culture and employeeperformance. The method which is used is a quantitatively method. The population of this studyis overall of UIN Sunan Kalijaga employees totaling 498 people, with a sample of 222 respondents.Research Location is UIN Sunan Kalijaga Yogyakarta. Techniques of data collection isdone by providing the questionnaire as the primary data and the the utilization of secondarydata (reports, magazines, etc.). Test the validity of data is done by using a correlation productmoment and the Cronbach Alpha reliability test (variables studied cronbach declared reliable ifthe value of alpha (?) is above the table or above r 0.600). Meanwhile the analysis using simplifiedlinear regression analysis. This analysis is used to measure the influence of organizationalculture on employee performance by use of a significant level (?) of 5%. From the researchresults that have been done acquired the following results: First, the relationship between OrganizationalCulture by Employee Performance of 0.619, and significant direction. Second, theeffect of frequency of Organizational Culture on Employee Performance by 38.3% remainder61.7% is influenced by the outside factors of this regression model. Third, the tendency forthe affected Employee Performance Organizational Culture generally experienced reductiondecline. Third, the tendencies for the affected Employees Performance are influenced by theOrganizational Culture generally experienced reduction.